PENERAPAN TELENURSING DALAM PELAYANAN KESEHATAN : Literature Review - Rizka Fadhila; Tuti Afriani (LPPM Universitas Abdurrab, 2020)
Abstract The development of information and communication technology has a big effect on the field of health, especially the field of nursing. Nurses are required to take advantage of technological developments one of them through telenursing service (telenursing). Telenursing is a component telehealth that occurs when nurses meet the health needs of clients using information communication technologies and web-based systems. Technologies that can be used in telenursing vary widely, including: telephones, personal digital assistants, smartphones, facsimile machines, tablets, computers, internet, video and audio conferencing, teleradiology dan computer information systems. The purpose of this paper is to find out the application of telenursing in health services.Writing method used is literature study which analyzed from several journals related to the topic taken. Journals are investigated through Proquest, Ebsco, Science Direct, and Clinical Key which are then selected according to the topics to be discussed. The results of the analysis indicate that the application of telenursing has a positive impact on public health. Telenursing allows to be applied in Indonesia in an effort to improve the quality of health service. Key word : information technology, telenursing, nurse Abstrak Perkembangan teknologi informasi dan komunikasi berpengaruh besar terhadap bidang kesehatan khususnya bidang keperawatan. Perawat dituntut untuk memanfaatkan perkembangan teknologi salah satunya melalui pelayanan keperawatan jarak jauh (telenursing). Telenursing adalah komponen telehealth yang terjadi ketika perawat memenuhi kebutuhan dasar klien dengan menggunakan teknologi informasi komunikasi dan sistem berbasis web. Teknologi yang dapat digunakan dalam telenursing sangat bervariasi, meliputi: telepon, personal digital assistants, smartphone, mesin faksimili, tablet, computer, internet, video dan audio conferencing, teleradiologi dan system informasi komputer. Tujuan penulisan ini adalah untuk mengetahui penerapan telenursing dalam pelayanan kesehatan. Metode penulisan yang digunakan adalah studi literatur yang dianalisis dari beberapa jurnal. yang terkait dengan topik yang diambil. Jurnal ditelurusi melalui Proquest, Ebsco, Science Direct, dan Clinical Key yang kemudian diseleksi sesuai dengan topik yang akan dibahas.Hasil analisis menunjukkan bahwa penerapan telenursing mempunyai dampak positif terhadap kesehatan masyarakat. Telenursing memungkinkan untuk diterapkan di Indonesia dalam upaya meningkatkan kualitas pelayanan kesehatan. Kata kunci : teknologi informasi, telenursing, perawat